Recht und Praxis der Schlichtung (chôtei) in Japan - Baum, Harald; Schwittek, Eva (Zeitschrift für Japanisches Recht, 2009)
Japan’s tradition of consensus-oriented settlement of disputes with the aid of a neutral intermediary is exceptionally long, though its institutionalised forms and functions have changed over time. Modern Japanese law contains two basic types of consensus-oriented settlement procedures: the court-related conciliation procedures (chôtei) on the one hand, and the various kinds of ADR-procedures (assen) offered by private institutions on the other. This article focuses on the institutional setting, regulation, and function of the court-related conciliation, with an emphasis on the Civil Conciliation (minji chôtei). After an introductory survey containing the historical development and the reasons for the wide acceptance of the Civil Conciliation, the authors thoroughly explain the procedure of the Civil Conciliation. They then analyse the selection criteria, role, and assignment of conciliators in Civil Conciliation. Following this, they present two special conciliation procedures in the fields of family matters and consumer indebtedness. Those special procedures are basically concordant with the Civil Conciliation procedure, but contain some special features to meet the particular problems, such as wider decision and enforcement possibilities with respect to recurrent performances in family matters, or the extended possibility to suspend civil enforcement procedures in order to enable avoidance of consumer insolvency. The authors conclude that the court-related conciliation successfully combines elements of traditional Japanese methods of dispute settlement with the legal institutions and procedures taken over from Continental Europe. The adjacency to the judicial proceedings is mainly organizational. The court can order a change to the Civil Conciliation procedure for a pending action – until the commencement of the court proceedings even against the parties’ will. In some matters of family law, the Civil Conciliation procedure is a mandatory preliminary proceeding.